Carbon nanotubes flow on mixed convection of aligned magnetohydrodynamics over a static/moving wedge with convective boundary conditions - Siti Shuhada, Ishak; Nurin Nisa, Mohd Noor Azhar; Nurul Syafiqah, Nazli; Mohd Rijal, Ilias; Roselah, Osman; Zubaidah, Sadikin; Abdul Rahman, Mohd Kasim; Nurul Farahain, Mohammad (Semarak Ilmu Publishing, 2023)
Nanotubes have been designed to be significantly larger than any other material, and these cylindrical carbon molecules have exceptional properties that are important for nanoscience and nanotechnology. Due to their exceptional thermal conductivity and mechanical and electrical properties, carbon nanotubes are used as additives to improve heat transfer in various industrial applications. The study analyzed a steady, two-dimensional, carbon nanotubes (CNTs) flow on aligned magnetohydrodynamics mixed convection over a static or moving wedge with convective boundary conditions. The CNTs used are single-wall carbon nanotubes (SWCNTs), multi-wall carbon nanotubes (MWCNTs), and water as the base fluid. The similarity transformation was used to reduce the partial differential governing equations into ordinary differential equations. Then, the reduced equations were solved using fourth-fifth order Runge– Kutta–Fehlberg and coded into Maple Software. The results of velocity and temperature profiles were illustrated graphically while the results of skin friction coefficient and Nusselt number were presented in tabulated data. It is found that the velocity profiles increase, and temperature profiles decrease when the angle of aligned magnetic field parameter, the interaction of magnetic parameter, convective parameter, and total angle of the wedge parameter number increase. For case where Biot number and volume fraction of nanoparticles parameters increase, the velocity profiles decrease, and temperature profiles increase. SWCNTs have increased skin friction and Nusselt numbers due to their higher density and thermal conductivity compared to MWCNTs. The finding of this study will benefit the who works in research and development in a range of industries and the mathematics body of knowledge as it provides new information to people who are interested in this field.